Software Reliability Assessment Based on the Evaluation of Operational Experience - Söhnlein, Sven; Saglietti, Francesca; Bitzer, Franz; Meitner, Matthias; Baryschew, Siegried (Measurement, Modelling, and Evaluation of Computing Systems and Dependability and Fault Tolerance, 2010)
This paper illustrates a practicable approach to reliability evaluation for highly reliable software systems based on the analysis of their operational experience and demonstrates its applicability to the control software of a gearbox system. The investigations were carried out within a cooperation of academia and automotive industry. The article also elaborates on the possibility of assessing software reliability at system level by combination of componentspecific software reliability estimate
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.lsinfs_1.softwa
Keywords: Component-based systems; Highly reliable software; Operational experience; Statistical testing